Outcomes of non-metastatic triple negative breast cancers: Real-world data from a large Indian cohort - Jyoti Bajpai; Lakhan Kashyap; Dilip Harindran Vallathol; Ankita Das; Maneesh Singh; Rima Pathak; Sushmita Rath; Anbarasan Sekar; Subham Mohanta; Asha Reddy; Shalaka Joshi; Ravindra Nandhana; et al. (Breast, 2022)
Background: Triple negative Breast tumor (TNBC) is an aggressive tumor with sparse data worldwide. Methods: We analyzed non-metastatic TNBC from 2013 to 2019 for demographics, practice patterns, and survival by the Kaplan Meir method. Prognostic factors for OS and DFS were evaluated using Cox Proportional Hazard model estimator for univariate and multivariable analysis after checking for collinearity among the variables. Results: There were 1297 patients with median age of 38 years; 41 (33.3%) among 123 tested were BRCA-positives. Among these 593 (45.7%) had stage III disease, 1279 (98.6%) were grade III, 165 (13.0%) had peri-nodal extension (PNE), 212 (16.0%) lympho-vascular invasion (LVI), and 21 (1.6%) were metaplastic; 1256 (96.8%) received chemotherapy including 820 (63.2%) neoadjuvant with 306 (40.0%) pCR. Grade ≥3 toxicities occurred in 155 (12.4%) including two deaths and 3 s-primaries. 1234 (95.2%) underwent surgery [722 (55.7%) breast conservations] and 1034 (79.7%) received radiotherapy.At a median follow-up of 54 months, median disease-free (DFS) was 92.2 months and overall survival (OS) was not reached. 5-year estimated DFS and OS was 65.9% and 80.3%. There were 259 (20.0%) failures; predominantly distant (204, 15.7%) - lung (51%), liver (31.8%).In multivariate analysis presence of LVI (HR-2.00, p-0.003), PNE (HR-2.09 p-0.003), older age (HR-1.03, p-0.002) and stage III disease (HR-4.89, p-0.027), were associated with poor OS. Conclusion: Relatively large contemporary data of non-metastatic TNBC confirms aggressive biology and predominant advanced stage presentation which adversely affects outcomes. The data strongly indicate the unmet need for early detection to optimize care.